IMPROVING STUDENT’S VOCABULARY USING FLASHCARDS FOR FOURTH GRADERS OF SDN PENDRIKAN LOR 02 SEMARANG - Oktovandi, Rahmad; Widyaningrum, Agnes (LINGUAMEDIA Journal, 2023)
The researcher has chosen to conduct this research because it will allow him to draw some inferences regarding the level of vocabulary knowledge among students at Pendrikan Lor 02 Elementary School. This research seeks to improve the vocabulary mastery of fourth graders at Pendrikan Lor 02 Elementary School since there is a problem with their vocabulary mastery and their interest in using flashcards. In this context, the researcher used CAR to enhance vocabulary acquisition in the classroom. He combined the flashcard approach with Classroom Action Research (CAR) for a more organized investigation. The study's results for the pre-test average score is 71.40, and the development of the post-test is 95,60. The flashcard technique and CAR were effective in this trial, yielding positive outcomes. The researcher used the CAR method to understand the classroom situation and the combination of CAR and TEYL to make the research more concrete.